2018
DOI: 10.1002/asl.823
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing of deep convection within a tropical‐like cyclone over the Mediterranean Sea

Abstract: The Mediterranean basin occasionally hosts tropical‐like cyclones named “Medicanes”. Medicanes may have intensity comparable to hurricanes in terms of wind speeds along with an axisymmetric cloud structure. Although these events can be particularly violent, very few studies so far have investigated the distribution and temporal evolution of deep convection within these cyclones. In this study, the characteristics and lifetime of deep convection and lightning activity surrounding the core of the longest‐lasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 23 publications
4
33
0
Order By: Relevance
“…As a consequence, one can estimate the deepening Δp of the minimum central pressure with time for a tropical cyclone, based on the change in e from the external region, where the parcel starts, to the cyclone centre, that is, from the undisturbed region to the area affected by intense air-sea interaction processes: Δp = −2.5Δ e . Thus, a change in e of around 10 K would cause a surface pressure drop of about 25 hPa; in our cases, one can observe a change of about 10-15 hPa in the two cyclones, which can be understood considering that the extent of the troposphere at midlatitudes (typically up to 300 hPa) is shallower compared to that in a typical tropical environment (up to 100 hPa), that convection in the mature stage of medicanes is often shallow (Miglietta et al, 2013;Dafis et al, 2018) and that the entrainment of dry air can be an important process in the midlatitudes. Thus, for the Mediterranean, this empirical relationship does not work, and its formula should be corrected based on a set of several case-studies.…”
Section: Discussionsupporting
confidence: 54%
“…As a consequence, one can estimate the deepening Δp of the minimum central pressure with time for a tropical cyclone, based on the change in e from the external region, where the parcel starts, to the cyclone centre, that is, from the undisturbed region to the area affected by intense air-sea interaction processes: Δp = −2.5Δ e . Thus, a change in e of around 10 K would cause a surface pressure drop of about 25 hPa; in our cases, one can observe a change of about 10-15 hPa in the two cyclones, which can be understood considering that the extent of the troposphere at midlatitudes (typically up to 300 hPa) is shallower compared to that in a typical tropical environment (up to 100 hPa), that convection in the mature stage of medicanes is often shallow (Miglietta et al, 2013;Dafis et al, 2018) and that the entrainment of dry air can be an important process in the midlatitudes. Thus, for the Mediterranean, this empirical relationship does not work, and its formula should be corrected based on a set of several case-studies.…”
Section: Discussionsupporting
confidence: 54%
“…Please clarify this point here and later in the discussion (L561-564 should be changed, as the Medicane apparently belongs to the second category of Medicanes). is consistent with the observations in Miglietta et al (2013) andDafis et al (2018).…”
supporting
confidence: 94%
“…Miglietta et al (2013) also came to similar results by investigating 14 MTLCs with a combined satellite-monitoring and modelling approach. The evolution of DC and lightning activity of the MTLC "ROLF" in 2011 was studied by Dafis et al (2018), who showed that the convective evolution of the cyclone shares more similar characteristics with TCs than intense extratropical Mediterranean cyclones.…”
Section: Introductionmentioning
confidence: 99%